ANALISIS PENGARUH MANAJEMEN RANTAI PASOK BAHAN BAKU TERHADAP KINERJA UMKM KERIPIK SINGKONG DI KOTA CILEGON - Purnama Sari, Wulan; Astuti, Andjar; Suherman, Suherman (CV. Era Digital Nusantara, 2022)
This study aims to analyze the relationship of information sharing, trust, long-term relationships, and collaboration on the performance of Micro, Small and Medium Enterprises (UMKM) cassava chips in the City of Cilegon. The number of samples in this study was 40 respondents, namely the owners of cassava chips Micro, Small and Medium Enterprises (UMKM) and directly related to cassava raw material suppliers. Data analysis techniques use multiple linear regression analysis.The analysis tools are using SPSS program version 21. Based on the results of the analysis that has been done, the results show that sharing information has a positive but not significant effect on the company's performance. The trust has a positive and significant effect on the company's performance. Long-term relationships have a positive but not significant effect on the company's performance. Collaboration has a positive and significant effect on the company's performance.